2017
DOI: 10.3906/sag-1603-101
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Parkinson disease: prevalence, temporal relationship, and determinants

Abstract: Background/aim: Comorbidity of depression in Parkinson disease (PD) is a major factor that changes patients' quality of life. However, the neurobiological and sociodemographic risk factors for this comorbidity are not well studied. In this study, we aimed to define the prevalence, temporal relationship, and psychosocial and clinical determinants of depression comorbid with PD.Materials and methods: Fifty-five PD patients were evaluated with SCID, a data form that assessed sociodemographic and PD-related variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…24,25,[27][28][29][30][31]38,40 It was to be found that the duration of PD symptoms was not related to depression, which supports the idea that depression might be a neuropathological process occurring concomitantly or before the degeneration of motor systems, which is similar with other study. 41 An interesting and surprising finding was that H-Y stage and disability was not associated with depression in multivariate logistic regression model but was significant in univariate analysis. Depression was higher in H-Y stages III and above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25,[27][28][29][30][31]38,40 It was to be found that the duration of PD symptoms was not related to depression, which supports the idea that depression might be a neuropathological process occurring concomitantly or before the degeneration of motor systems, which is similar with other study. 41 An interesting and surprising finding was that H-Y stage and disability was not associated with depression in multivariate logistic regression model but was significant in univariate analysis. Depression was higher in H-Y stages III and above.…”
Section: Discussionmentioning
confidence: 99%
“…3,[18][19][20] Depression also has an impact on motor deficits, disability, caregiver burden, economic strain, cognitive impairment and severity of medical illness. 21,22,38,40,41 It is likely that depression in PD is multifactorial which includes age, sex, disease severity, longer disease duration, a younger PD onset age, frequent fall, lower education level, smoking and regular use of non-aspirin bases NSAIDs or analgesics. [23][24][25][26][27][28][29][30][31] Whereas a recent study reported that PD patients with depression were associated with different demographic and clinical factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is a frequent NMS in both early and advanced stages of PD [ 4 ] and may represent a pre-motor marker of the disease [ 5 ]. The occurrence of depression in PD is associated with increased risk of late-stage complications, such as dementia, falls, and caregiver distress [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested that depressive symptoms may precede the diagnosis of PD by 5 up to 20 years, and MDD has been associated with an increased risk of developing PD with an incidence of 23% (Chaudhuri et al, 2006;Pellicano et al, 2007;Postuma et al, 2012;Chen et al, 2013;Pont-Sunyer et al, 2015). Once PD is diagnosed, the annual rates of newly diagnosed MDD range from 1.86 to 10% (Aarsland et al, 2011;Marsh, 2013;Yapici Eser et al, 2017) and studies have shown that MDD tends to be persistent and worsens over time (Aarsland et al, 2011). Although the exact etiology is unknown, several hypotheses supporting the link between MDD and PD physiopathology have been proposed (Aarsland et al, 2011;Santiago et al, 2017).…”
Section: Mdd and Parkinson's Diseasementioning
confidence: 99%